Identification of functional domains in developmental measures: An ICF-CY analysis of Griffiths developmental scales and Schedule of Growing Skills II. (3rd July 2016) - Castro, Susana; Coelho, Vera; Pinto, Ana
Abstract: Objective : This study aims to identify functioning categories of the International Classification of Functionality, Disability and Health for Children and Youth covered by the Griffiths developmental scales and the Schedule of Growing Skills II (SGS-II), as well as to analyse levels of agreement between coders when assigning its items to the ICF-CY classification system. Methods : Items were linked to the ICF-CY following a content analysis procedure and the published linking rules. Agreement was calculated with Cohen's Kappa Coefficient. Results : All SGS items assess mostly Activities and Participation, alike most of the Griffiths' scales except for the Language and Eye-hand coordination scales, which assess mostly Body Functions. Consistently with previous studies, agreement levels between coders vary considerably, thus being highly dependent on the nature of the concept analysed. Conclusion : Although necessary from a capacity-driven approach to assessment, information collected with these instruments should be complemented with other assessments in order to cover all aspects of the child's life, in line with a systemic approach.